VEEP. The final season [videorecording (DVD)] - Iannucci, Armando, 1963- (HBO Home Video, 2020)
The show follows Meyer and her staff as they attempt to make their mark and leave a lasting legacy, without getting tripped up in the day-to-day political games that define Washington.